OPTIMIZATION OF A SOLID PREPARE OF DIETARY FIBER FROM DIFFERENT REMAINDERS OF FRUITS - FLÓREZ A., Oscar; ROMÁN M., Orfilia; MARTÍNEZ, Olga L.; GUTIÉRREZ E., Lucía; MEDINA, Gilma B. (Vitae, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; @font-face font-family:Aldine401BT-RomanA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 134676480 16 0 131073 0; @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; @font-face font-family:"\@Aldine401BT-RomanA"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> In this work a procedure to optimize the physicochemical and nutritional characteristics of several dietary fiber sources, which are processed as tablets, is presented. Optimization means the use of a series of mathematical techniques for reducing the number of variables to one or to a minimum number of them in such way that the most suitable answer among several possible ones be obtained. In this study a method is used that involves a linear summation of percentages and makes an analysis of the main components (AMC) or fiber sources. The method evaluates how many of the initial fiber sources are needed in order to preserve the optimum nutritional benefit that is expected from the fiber tablet elaborated by adjusting the quantities of different fiber sources. With this method it is shown that by using only maracuyá fruit remainders it is possible to obtain a tablet optimized as far as its functional characteristics and the use of resources, compared with the obtained one from mixtures of other 5 dietary fibers.